Improved meet-in-the-middle attack on reduced-round Kiasu-BC algorithm - Manman LI; Shaozhen CHEN (Tongxin xuebao)
Kiasu-BC algorithm is an internal tweakable block cipher of authenticated encryption algorithm Kiasu as one of first-round candidates in the CAESAR competition.The precomputation complexity is reduced by utilizing the freedom of the tweak and the internal key restriction through the research on structural characteristics of Kiasu-BC algorithm based on AES-128 round function.Combined with the differential enumeration technique, a new 5-round meet-in-the-middle distinguisher was constructed to improve the meet-in-the-middle attack on 8-round Kiasu-BC algorithm.The improved attack requires the time complexity of 2114, the memory complexity of 263 and the data complexity of 2108.